(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
Numerous factors lead to the use of water with saline levels above those suitable for plant development, resulting in negative consequences on crops. Studies have sought techniques that aim to mitigate such consequences and the use of vitamins is promising, since these compounds improve the conditions of vegetables. Thus, the study aimed to verify the ability of vitamins to mitigate the deleterious effects of using saline water, applied via irrigation during the formation of cucumber seedlings. Cucumber seeds were subjected to imbibition in three vitamin solutions (100 mg L-1 thiamine; 100 mg L-1 niacin; 50 mg L-1 thiamine + 50 mg L-1 niacin), in addition to two controls, both with water imbibition . After sowing, irrigation was carried out with saline water (100 mM NaCl), for all treatments, except for one of the controls. It was found that irrigation with saline water affected all variables studied, without, however, having a positive effect from the application of vitamins. Thus, it was concluded that the vitamins were not able to mitigate the deleterious effects caused by the application of saline water under the conditions in which the study was carried out and that future studies should be carried out to evaluate different concentrations and forms of application of the vitamins.